(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Type 2 diabetes mellitus demonstrates significant associations with cognitive deterioration across multiple neuropsychological domains. This investigation examined specific patterns of cognitive dysfunction in diabetic populations through comprehensive neuropsychological assessment and metabolic parameter analysis. The study evaluated 127 patients with established type 2 diabetes and 85 matched controls, revealing distinct executive function deficits, working memory impairment, and processing speed reduction in the diabetic cohort. Glycemic control quality correlated inversely with cognitive performance metrics, while disease duration predicted progressive cognitive decline trajectories. These findings underscore the clinical imperative for systematic cognitive screening and metabolic optimization strategies in diabetes management protocols.